Biomarker Panel for Early Detection in Uterine Cancer: A Review - priya, N. Deepthi; Nanda Kumar, K. V.; Charani, M. Siva; Bindu, D.; Reddy, K. Likhitha; Gowthami, Y. (Asian Pacific Journal of Cancer Biology, 2024)
Uterine cancer is the numerous prevalent cancers of the female reproductive tract in industrialized as well as developing countries and its probability is arising annually. There is a total of approximated 90,000 mortality and 382,000 instances newly cases treated annually globally. The desire to create and define biological markers for the initial stages detection and therapy of uterine cancer is growing. We analyze the current state of biomarker utilization for early detection, including their sensitivity and specificity, paving the way for timely interventions. Several biomarkers, including P53, K-RAS, CA-125, HER2/neu, HE4, PTEN, MSI, ARID1A,Ki-67, microRNAs, DNA aneuploidy, estrogen and progesterone receptors are used for early detection, treatment, and prevention of uterine cancer. Oncogene biomarkers such as VEGF, Hypoxia-inducible factor-1α (HIF-1α), and PI3K-AKT- mTOR signalling pathways plays a crucial roles in cancer progression, offering promising targets for therapeutic intervention and prognostic assessment. Prognostic and emerging biomarkers L1CAM, MMR proteins, CTCs shed form primary tumors into the bloodstream, offer insights into tumour dissemination and treatment response. In conclusion, early detection through all biomarkers holds great promise for early diagnosis and treatment advancements, as well as providing hope for better results and a higher standard of living for individuals in future generations. This review aims to provide a holistic understanding of uterine cancer biology and its clinical implications.